Problematika Penerimaan Komuni bagi Orang Berkebutuhan Khusus (OBK) dan Pemahaman dari Para Prodiakon - Yohanes Subali; Vergilius Seto Adi Purwono; Atanasius Yubileum Agung (Studia Philosophica et Theologica, 2023)
People with Special Needs (OBK) are individuals who have limitations or extraordinary abilities, both physically, mentally-intellectually, socially, or emotionally, which have a significant influence on their growth or development process compared to people in general. OBK is also often referred to as persons with disabilities. Even so, OBK are God's good creatures. With this awareness, OBK should have rights and obligations in their lives, especially in church life. With the limitations and specialties they have, OBK can take part in Church tasks thanks to the Sacrament of Baptism which is obtained according to their abilities. In addition, the rights as citizens of the Church also need to be considered. However, the people's perception of OBK is that there is still a tension of understanding. Pros and cons occur because of the assumption that OBK are still worthy of receiving Communion but there is also an assumption that OBK are unfit to receive sacramental services in and by the Church. This article is a research on the perceptions of the parishioners in several parishes in the Vicarage of the Special Region of Yogyakarta as a part of Archdiocese of Semarang for receiving Communion to parishioners who experience mental limitations. The research method used is quantitative methods. The purpose of this research is to make Catholics aware that OBK are God's good creations and they also have rights and obligations in the Church according to their abilities thanks to the Sacrament of Baptism they receive. The mission of OBK as Christian faithful is written in LG 10, book of canon law Canon 204, book of canon law Canon 208. Even so, there needs to be further assessment from psychologists, counselors, priests, and catechists to measure the extent to which CBOs are able to differentiate with their minds between the host or the Body of Christ as the main requirement for receiving Communion during the Eucharistic Celebration.